2019
DOI: 10.1002/ajcp.12397
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Role of Mentees’ Social Skills and Relationship Quality in a School‐Based Mentoring Program

Abstract: Research on youth mentoring highlights the importance of the relationship quality between mentor and mentee; mentoring results in more positive outcomes when the mentee perceives the relationship as satisfying and trustworthy. Research on relationship quality shows that social skills are important for constructing new relationships. However, whereas improved social skills are often one of the main goals of youth mentoring, little is known about the importance of social skills for relationship quality in youth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
0
11
0
2
Order By: Relevance
“…Similarly, research on youths' perception of the quality of the mentoring relationship affects their own outcomes (e.g. Eby et al, 2013;Lyons et al, 2019;Schenk et al, 2019). Considering that mentors are affected by the quality of the relationship and likely derive benefit from it, it is logical to examine whether the relationship may also affect students' flourishing.…”
Section: Mentoring Relationship Qualitymentioning
confidence: 99%
“…Similarly, research on youths' perception of the quality of the mentoring relationship affects their own outcomes (e.g. Eby et al, 2013;Lyons et al, 2019;Schenk et al, 2019). Considering that mentors are affected by the quality of the relationship and likely derive benefit from it, it is logical to examine whether the relationship may also affect students' flourishing.…”
Section: Mentoring Relationship Qualitymentioning
confidence: 99%
“…4.1 | Quality mentoring relationships, maternal relationship characteristics, and youth outcomes: Building a mediated model As maternal relationships characteristics have been found to affect the quality of the mentoring relationship (Williamson et al, 2019), and quality mentoring relationships are associated with behavioral and academic outcomes (Deutsch et al, 2016;Raposa et al, 2019;Seiving et al, 2016;Schenk et al, 2020), it follows that the association between maternal relationship characteristics and behavioral and academic outcomes could be mediated by the mentoring relationship quality (see Figure 1). This gap is notable, because mentoring programs may choose to adjust the types of training and support offered to mentors and mentees beginning a mentoring relationship depending on the strength and type of prior parental relationships.…”
Section: Current Studymentioning
confidence: 99%
“…This suggests that a mentor as an additional social support could be beneficial in protecting against the relational difficulties experienced by early adolescent girls. In fact, according to a prior school‐based mentoring program, girls reported that their mentors helped them improve their relational skills and development, such as increasing their ability to trust people and improving social skills (Deutsch et al, 2016; Schenk et al, 2020). Strong mentoring relationships have been found to be associated with improvement in youths' parental and teacher relationships as well as an improvement in social skills and behaviors (Chan et al, 2013; Seiving et al, 2016).…”
Section: Adolescent Developmental Outcomes and Youth Mentoringmentioning
confidence: 99%
“…Within mentoring relationships, relationship quality stands out as an important factor with respect to both short‐term and long‐term outcomes for mentees (DuBois et al, 2002; Eby et al, 2013; Goldner & Mayseless, 2009; Schenk et al, 2020; Silke et al, 2019). Eby et al (2013) conducted a meta‐analysis of studies across three different mentoring contexts (mentoring with youth populations, in an academic setting, and within the workplace).…”
Section: Introductionmentioning
confidence: 99%